Welcoming a New Era of Education: The Implementation of the Merdeka Curriculum in Elementary Schools - Arini Mulkisam; Fitrah Auliya (Journal of Primary Education Innovation and Research, 2025)
This article explores the challenges and opportunities in welcoming a new era of education through the implementation of the Merdeka Curriculum in elementary schools. The main focus is on curriculum flexibility, project-based learning, the development of 21st-century skills, community involvement, and formative assessment. This study employed a literature review method as the data collection technique by searching for related articles or journals. Through this approach, this article emphasizes the importance of transforming the learning paradigm toward equity, relevance, and students’ active participation. The concrete steps proposed strengthen collaboration among schools, parents, and local communities to create an inclusive and innovative educational environment. In conclusion, the implementation of the Merdeka Curriculum in elementary schools serves as a strong foundation for preparing future generations to face global challenges with confidence and relevant skills.